Further notes on the capture of a Carcharhinus leucas in a northeastern Atlantic oceanic insular shelf, the Azores Archipelago, Portugal - Gadig, Otto B.F. [UNESP]; Juliano, Manuela F.; Barreiros, João P. (My University, 2006)
In March 1993, a specimen of Carcharhinus leucas was captured by fishermen on the south coast of Terceira Island, the Azores Archipelago. Its head was recovered and its jaws were preserved. This is the first capture of this species on an oceanic insular shelf in the Atlantic. The distribution of C. leucas in this ocean is commented.
Keywords: Azores Archipelago; Carcharhinidae; Carcharhinus leucas; First record; NE Atlantic